(untitled) (Research, Society and Development, 2022)
Gloves used in health care are indicated as a protective barrier for health professionals, especially biological risk, and are part of Personal Protective Equipment. The performance of dressings aims to protect the injury or wound from the action of external agents and may be physical, chemical or biological, besides providing cleaning, absorption of exudatos, immobilization and pain relief. Three different types of materials can be used: dressing kit, sterile glove and procedure glove. The study is an integrative review of the literature, is based on the question: What is the importance of the practice of the use of sterile gloves by nurses in the performance of dressings in the hospital environment? It aims to seek scientific evidence in the light of the literature that allows analyzing the practice of the use of sterile glove by nurses to perform dressings and the effectiveness of the sterile technique in this procedure. There are no absolute concepts regarding the clean and sterile technique in the most diverse situations in which patients can present. However, it can be understood that the practice of stereo technique in the hospital environment becomes safer for the prevention of infections in skin wounds. And that the use of sterile gloves cannot be classified as an incorrect technique.